The characteristics of cod feeding in the Eastern Baltic and its influence on the herring and sprat stocks - Uzars, D.V.; Lishev, M.N. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1967)
The work is based on the material sampled during the spawning and feeding periods of cod Gadus morhua in 1963-1965. The qualitative and quantitative composition, the spatial and temporal (in different seasons and age groups) variation of cod feeding in the Eastern Baltic is described. It was concluded that cod exerts direct impact upon the herring Clupea harengus stock of the Northeastern and Eastern Baltic. Also, a well-expressed dependence between the sprat Sprattus sprattus catches and cod abundance was found. On that account it was assumed that the abundance dynamics of sprat stock is considerably influenced by cod abundance. Published Not Known